Development of Traditional Market Organizational Design Model in Bandung Regency - Thomas Bustomi; Dafa Ramadhan; Resta Berlian; Iis Hernawati (Journal of Public Administration and Government, 2023)
The functionality of traditional markets has recently experienced a decline, resulting in their slow displacement by modern markets. This prompts an intriguing exploration through this research to develop a comprehensive market organization design model in Bandung Regency, focusing on the input, matching, and decision stages. Utilizing an organizational approach provides an overview of the research's objectives, which include: 1) understanding, describing, and analyzing internal and external environmental factors influencing market organizations, 2) identifying organizational strategic issues faced by the Bandung Regency Industry and Trade Service, and 3) generating alternative organizational strategies for market management in Bandung Regency. This research employs a qualitative method with a phenomenological approach, examining markets neighboring Bandung City and Cimahi City. Internal and external organizational factors dominant in market management in Bandung Regency were identified. These factors contribute to several organizational strategic issues faced by the Bandung Regency Industry and Trade Service in managing markets in border areas. These issues include traditional markets not meeting the 3K standards (Health, Comfort, and Safety), a weak organizational chain in market management, and positive impacts of advancements in science and information technology, particularly the use of computerized systems, on enhancing organizational efficiency. To address these organizational strategic issues, the research formulates five reliable strategic alternatives for solving market management problems on the borders of Bandung Regency.